Induction of PR-proteins and defense related enzymes in black pepper due to inoculation with Phytophthora capsici - M. ANANDARAJ and Y.R. SARMA, R. STEPHEN JEBAKUMAR, (Indian Phytopathology, 2002)
The activities of phenylalanine ammonia lyase (PAL) and 61,3 glucanase in both leaf and root tissues of three black pepper varieties (tolerant P24; and susceptible Panniyur! and Subhakara) were determined in healthy and Phytophthora capsici infected tissues. Infection generally enhanced both of these enzyme activities. SDS-PAGE study revealed the induction of PR-proteins in the infected tissues. Western blotting with anti-tobacco 61,3 glucanase antibody confirmed the presence of these isoforms in the leaf extract. Among the three varieties studied, the Phytophthora tolerant P24 expressed higher rate of these defense-related enzymes/proteins.